2019
DOI: 10.1016/j.neuropsychologia.2019.107124
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the role of the posterior medial frontal cortex in social conflict processing

Abstract: A fundamental function of the brain is learning via new information. Studies investigating the 22 neural basis of information-based learning processes indicate an important role played by the 23 posterior medial frontal cortex (pMFC) in representing conflict between an individual's 24 expectation and new information. However, specific function of the pMFC in this process 25 remains relatively indistinct. Particularly, it's unclear whether the pMFC plays a role in the 26 detection of conflict of incoming inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 59 publications
3
7
0
Order By: Relevance
“…Consistent with the previous works, we found a significant conformity effect; the second ratings of the participants were significantly influenced by the group rating even after the regression-to-the-mean effect was controlled (t(24) = 2.18, p = 0.02, d = 0.43). We also found highly significant regression-to-the-mean effect (t(24) = -15.81, p < 0.001, d = 3.16), which is consistent with our previous studies [4,5]. During the reinforcement learning task, participants selected options with a higher reward probability 59.9 % of the trials, which is significantly higher than the chance (50%; t(24) = 6.22, p < 0.001, d = 1.24), indicating that the participants were generally able to accurately keep track of the fluctuating reward probabilities based on reward outcomes.…”
Section: Behavioral Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with the previous works, we found a significant conformity effect; the second ratings of the participants were significantly influenced by the group rating even after the regression-to-the-mean effect was controlled (t(24) = 2.18, p = 0.02, d = 0.43). We also found highly significant regression-to-the-mean effect (t(24) = -15.81, p < 0.001, d = 3.16), which is consistent with our previous studies [4,5]. During the reinforcement learning task, participants selected options with a higher reward probability 59.9 % of the trials, which is significantly higher than the chance (50%; t(24) = 6.22, p < 0.001, d = 1.24), indicating that the participants were generally able to accurately keep track of the fluctuating reward probabilities based on reward outcomes.…”
Section: Behavioral Resultssupporting
confidence: 92%
“…The dependent variable was rating change (participant's second rating -first rating). The first rating was considered as one of the predictor variables to control for the regression-to-the-mean effect [4,5]. On the rare occasion (0.32% across all participants), seven participants pressed the decide button (right thump button) before the right or left key (i.e., they submitted their rating, most likely accidentally, when the cursor was still invisible).…”
Section: Behavioral Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on social conformity that used transcranial magnetic stimulation, it was shown that the pMFC plays a causal role in preference change (Klucharev, Munneke, Smidts, & Fernandez, 2011). Using the similar experimental paradigm, several studies have replicated the original fMRI findings (e.g., Campbell‐Meiklejohn, Bach, Roepstorff, Dolan, & Frith, 2010; Izuma & Adolphs, 2013; Korn et al, 2014; Korn, Prehn, Park, Walter, & Heekeren, 2012; Wake, Aoki, Nakahara, & Izuma, 2019), and a recent meta‐analysis revealed that the insula and pMFC are consistently positively related to social conflict (i.e., the difference between individual and group opinions) and that the ventral striatum is negatively related to social conflict (Wu, Luo, & Feng, 2016).…”
Section: Introductionmentioning
confidence: 78%
“…The dependent variable was rating change (participant's second rating ‐ first rating). The first rating was considered as one of the predictor variables to control for the regression‐to‐the‐mean effect (Izuma & Adolphs, 2013; Wake et al, 2019). On the rare occasion (0.32% across all participants), seven participants pressed the decide button (right thump button) before the right or left key (i.e., they submitted their rating, most likely accidentally, when the cursor was still invisible).…”
Section: Methodsmentioning
confidence: 99%